Dopamine Release in the Medial Preoptic Area is Related to Hormonal Action and Sexual Motivation. - Kleitz-Nelson, Hayley K.; Dominguez, Juan M.; Ball, Gregory F. (Behavioral Neuroscience, 2010)
To help elucidate how general the role of dopamine (DA) release in the medial preoptic area (mPOA) is for the activation of male sexual behavior in vertebrates, we recently developed an in vivo microdialysis procedure in the mPOA of Japanese quail. Using these techniques in the present experiment, the temporal pattern of DA release in relation to the precopulatory exposure to a female and to the expression of both appetitive and consummatory aspects of male sexual behavior was investigated. Extracellular samples from the mPOA of adult sexually experienced male quail were collected every 6 min before, while viewing, while in physical contact with, and after exposure to a female. In the absence of a precopulatory rise in DA, males failed to copulate when the barrier separating them from the female was removed. In contrast, males that showed a substantial increase in mPOA DA during precopulatory interactions behind the barrier, copulated with females after its removal. However, there was no difference in DA during periods when the quail were copulating as compared to when the female was present but the males were not copulating. In addition, we show that precopulatory DA predicts future DA levels and copulatory behavior frequency. Furthermore, the size of the cloacal gland, an accurate indicator of testosterone action, is positively correlated with precopulatory DA. Taken together, these results provide further support for the hypothesis that DA action in the mPOA is specifically linked to sexual motivation as compared to copulatory behavior per se. Reprinted by permission of the publisher.